Homologous Banked Bone Grafts for the Reconstruction of Large Cranial Defects in Pediatric Patients. Issue 8 (November 2018) - Canzi, Gabriele; Talamonti, Giuseppe; Mazzoleni, Fabio; Bozzetti, Alberto; Sozzi, Davide
Abstract : Purpose: Autogenous bone represents the best material in pediatric reconstructive cranioplasty because of its compatibility with growth; however, its availability is limited. Alternative use of alloplastic materials would have the advantage of unlimited amount, but shows an increased risk of complications and incompatibility with growth. Fresh frozen banked cadaveric bones could be ideal for the reconstruction of large cranial defects in growing patients, because it offers unlimited amount of structural grafts with biomechanics properties quite similar to the autologous bones. Results: The authors report 2 cases of growing patients (13 months female and 9 years old male) undergoing the reconstruction of large (about 70 cm 2 and 50 cm 2 respectively) cranial vault defects, by using structural homologous banked bone grafts. Analytic main reconstruction materials risks/benefits evaluation, literature review of few previously reported pediatric cranioplasty with homologous bone, and both clinical cases satisfactory radiologic long-term results (beyond 4 years of F.U.) are reported. Conclusion: Structural homologous banked bone grafts appear as a valid solution for pediatric canioplasty reconstruction of wide defects, entailing the advantages of available without limitations and compatibility with future growth. The risk of transmissible infections seems minimal and is totally counterbalanced by the stability of long-term results.